2011
DOI: 10.1111/j.1471-4159.2011.07257.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor protects retinal ganglion cells by increasing neuronal survival and axonal regeneration in vitro and in vivo

Abstract: Hepatocyte growth factor (HGF) is known to promote the survival and foster neuritic outgrowth of different subpopulations of CNS neurons during development. Together with its corresponding receptor c-mesenchymal-epithelial transition factor (Met), it is expressed in the developing and the adult murine, rat and human CNS. We have studied the role of HGF in paradigms of retinal ganglion cell (RGC) regeneration and cell death in vitro and in vivo. After application of recombinant HGF in vitro, survival of serum-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 41 publications
0
36
0
1
Order By: Relevance
“…PI3K-dependent Akt phosphorylation and subsequent increased synthesis of anti-apoptotic bcl proteins represents a common mechanism of regulating RGC survival shared by many growth factors such as BDNF, IGF, CNTF, HGF [23], [70][73], and cytokines such as IL-1β and erythropoietin [74], [75]. Recent studies have shown that the Akt isoforms, 1, 2, and 3 are present in the RGC layer in the rat retina, and all three subtypes are able to block RGC apoptosis after RIRI [76].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K-dependent Akt phosphorylation and subsequent increased synthesis of anti-apoptotic bcl proteins represents a common mechanism of regulating RGC survival shared by many growth factors such as BDNF, IGF, CNTF, HGF [23], [70][73], and cytokines such as IL-1β and erythropoietin [74], [75]. Recent studies have shown that the Akt isoforms, 1, 2, and 3 are present in the RGC layer in the rat retina, and all three subtypes are able to block RGC apoptosis after RIRI [76].…”
Section: Discussionmentioning
confidence: 99%
“…These changes should result from the activity of retinal neuronal cells and, not by only astrocytes considering the abundance of astrocytes in the retina. It has been reported that c-met , a HGF receptor gene, was present in RGCs and exogenous HGF protected RGCs through HGF receptor signaling 24, 25 . Therefore, progranulin may contribute to the direct protection of RGCs through HGF receptor signaling at immature stage followed by the activation of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mixture of type-1 collagen and b-TCP was expected to provide a biodegradable scaffold for local delivery of HGF. On the other hand, previous studies using local administration of HGF in various models in different species including rabbit revealed significant therapeutic effects of 100 lg HGF [11,[31][32][33][34]. Therefore, we selected a dose of 100 lg HGF/injection for the HGF/b-TCP/collagen complex because HGF was expected to exert biological effects and we could evaluate if HGF would have therapeutic benefits in this rabbit model.…”
Section: Discussionmentioning
confidence: 99%